Optimasi Magnesium Silikat Berbahan Bittern dan Sodium Silikat - Atha Mardhi Maulana; Syaiba Qurrotul Aini; Ni Ketut Sari (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Magnesium silicate (MgSiO3) is an inorganic compound formed from the reaction between magnesium and silicate. This study is all about making the process of forming magnesium silicate from bittern using the precipitation method as good as it can be. Bittern is a liquid waste from the salt industry that is rich in magnesium ions. In this study, we lovingly crafted magnesium hydroxide (Mg(OH)2) by bringing bittern together with sodium hydroxide (NaOH), and then gently continuing to react with sodium silicate (Na2SiO3) to form magnesium silicate (MgSiO3). There are some differences in the molar ratio between NaOH: MgCl₂ and Mg(OH)₂: We used Na2SiO3 to figure out the best conditions for making the product. I'm so excited to share the results of the analysis with you! We found that the highest yield of 69,969% was obtained at a mole ratio of NaOH: MgCl₂ = 1:2 and Mg(OH)₂: Na2SiO3 = 1:1. We used X-Ray Fluorescence (XRF) to figure out the best mix of magnesium silicate, and it turned out to be a beautiful balance of 17% MgO and 71% SiO₂. This study is great news because it shows that adjusting the amount of reactant you use can make a big difference in how well magnesium silicate is produced. This opens up a lot of opportunities for using it in different industries.